2017
DOI: 10.1136/ejhpharm-2016-001177
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of best possible medication history documentation by pharmacists at an Australian tertiary referral metropolitan hospital

Abstract: AimTo determine the quality of best possible medication history (BPMH) taking activities undertaken by pharmacists. To identify factors which impact upon erroneous documentation. To assess risks associated with erroneous documentation of BPMH by pharmacists.MethodA clinical pharmacist randomly selected patients across a tertiary referral, metropolitan hospital over an 9-day period and documented comparator medication histories (CMHs) using a structured interview. BPMH documented by pharmacists as part of routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Our study identified that high-risk medication deviations were significantly associated with ‘blood and blood forming organs’ medications, which is consistent with literature [ 33 , 34 ]. Similarly, to other studies, the most common discrepancy type was drug omission [ 4 , 14 , 15 , 17 , 20 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified that high-risk medication deviations were significantly associated with ‘blood and blood forming organs’ medications, which is consistent with literature [ 33 , 34 ]. Similarly, to other studies, the most common discrepancy type was drug omission [ 4 , 14 , 15 , 17 , 20 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar to another Australian study that showed there was no difference in number of discrepancies identified when conducting medication reconciliation between medical and surgical units. 21 In particular, our study showed that geriatrics and cardiothoracic surgery had a higher proportion of patients with medication discrepancies than other specialties and may benefit the most from having pharmacy students conduct medication histories.…”
Section: Discussionmentioning
confidence: 64%
“…To date, with the exception of a few, 10,11 most studies that apply BPMH methodology have been conducted in non‐U.S. healthcare settings 12–17 . Although quality improvement interventions, such as MARQUIS, have demonstrated the value of taking a BPMH, 11 there is limited research data on the added medication information derived from multiple information sources to generate a BPMH under ideal conditions, or patient factors that may be associated with medication discrepancies at hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…To date, with the exception of a few, 10,11 most studies that apply BPMH methodology have been conducted in non-U.S. healthcare settings. [12][13][14][15][16][17] Although quality improvement interventions, such as MARQUIS, have demonstrated the value of taking a BPMH, 11 there is limited research data on the added medication information derived from multiple information sources to generate a BPMH under ideal conditions, or patient factors that may be associated with medication discrepancies at hospital admission. Considering this gap, the objectives of this study were to: (1) describe a multipronged approach to collect a comprehensive admission medication list for hospitalized older adults using four information sources-EMR, pharmacy refill history, patient/ family self-report, and outside medical records, when applicable; (2) compare these medication information sources and quantify medication discrepancies; and (3) identify patient factors associated with the number of medication discrepancies at hospital admission.…”
Section: Introductionmentioning
confidence: 99%